2021
DOI: 10.3389/fcvm.2021.645541
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiles in Normotensive and Hypertensive South African Individuals

Abstract: Hypertension has a complex pathogenesis and symptoms appear in advanced disease. Dysregulation of gene expression regulatory factors like microRNAs has been reported in disease development. Identifying biomarkers which could help understand the pathogenesis and prognosis of hypertension is essential. The study's objective was to investigate microRNA expression profiles according to participant blood pressure status. Next generation sequencing was used to identify microRNAs in the whole blood of 48 body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Herein, we investigated circulating levels of miR-1299, miR-30a-5p, miR-30e-3p, miR-126-3p, and miR-182-5p in participants with normal blood pressure, as well as screen-detected and known hypertensives on anti-hypertensive treatment. These miRNAs were chosen as possible targets in our study as next generation sequencing data had previously shown their association with diabetes and HPT ( Matsha et al, 2018 ; Matshazi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we investigated circulating levels of miR-1299, miR-30a-5p, miR-30e-3p, miR-126-3p, and miR-182-5p in participants with normal blood pressure, as well as screen-detected and known hypertensives on anti-hypertensive treatment. These miRNAs were chosen as possible targets in our study as next generation sequencing data had previously shown their association with diabetes and HPT ( Matsha et al, 2018 ; Matshazi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, decreased levels of cardiac-enriched miR-133a are associated with the development of left ventricular hypertrophy in patients with arterial hypertension [11]. Several circulating miRNAs (miR-145, miR-4516, miR-1299, and miR-30a-5p) are regulated in primary hypertension [12][13][14]. Out of 21 deregulated cir-culating miRNAs in hypertensive patients, 4 of them are associated with albuminuria, indicating renal damage [15].…”
Section: Introductionmentioning
confidence: 99%